Rapidly progressive glomerulonephritis in a child with Henoch-Schönlein Vasculitis and familial Mediterranean fever - Kara Orhan; Ertan Pelin; Mir Sevgi; Sozeri Betul; Sen Sait (BMC, 2009)
Abstract Henoch-Schonlein Vasculitis (HSV) is systemic small vessel vasculitis involving the skin, kidney, joints, and gastrointestinal tract. The proportion of patients reported to have renal involvement varies between 20% and 80%. Rapidly progressive glomerulonephritis (RPGN)is rare syndrome in children, characterized by clinical features of glomerulonephritis (GN) and rapid loss of renal function. We present a severe kidney involvement in a 14 year old boy with HSV in who is carring MEFV mutation. A 14 year old boy had developed sudden onset of palpable purpuric rash on his extensor surfaces of lower extremities. He had elevated an erythrocyte sedimentation rate (ESR) (45 mm/h), C-reactive protein (3.74 mg/dl), serum urea 66 mg/dl, serum creatinine 1.8 mg/dl. Also, he had hypocomplementemia. Antinuclear antibody, anti ds DNA, antineutrophil cytoplasmic antibody, anticardiolipine antibodies were negative. Urinalysis revealed macroscopic hematuria and proteinuria with a 24-h urinary protein excretion of 55 mg/m2/h. The renal biopsy specimen showed crescentic and necrotizing glomerulonephritis. He had also M694V/E148Q compound heterozygote mutation. Clinical symptoms and renal failure resolved with intermittant hemodialysis and medical therapy.